‘Think of it as a Challenge’ : Problematizing Pedagogical Strategies for Progression when Assessing Web-based University Courses in Literary Studies - Svensson, Anette ; 0000-0002-6665-3990; Manderstedt, Lena; Palo, Annbritt (Læring og Medier, 2015)
The aim of this study is to analyse how a taxonomy-based course design can support students’ qualitative learning processes in online university courses. The paper presents a case study based on two online courses in comparative literature in Swedish and English. A document analysis has been applied to analyse the empirical material, which includes the syllabuses, study guides, and examination assignments connected to the courses. Socio-cultural aspects of learning processes, assessment and feedback, course design using a taxonomic structure (SOLO), and a progressive theory of literary studies (Langer’s theories of envisionment) function as a framework. The results show that the examination assignments aim to further the students’ educational processes from stage 2 to stage 5 of the SOLO-taxonomy and, at the same time, through Langer’s four stances. While the course structure has a positive effect on the students’ general as well as literary progress, there are some pedagogical challenges with online teaching in literature that are discussed. In addition, the examination assignments could have been used as ways to strengthen the students’ socio-cultural learning. Furthermore, with little alterations, the examination assignments, which were all used as means of summative assessment, could also have been used formatively to assess the students’ progress.
Keywords: Litteraturdidaktik